Analyzing the content of some Islamic advocacy sites on the Internet - A descriptive study: Islam Today website, the preaching diary website, and Dar Al Salam site for the Islamic Call - Alhamami, Hashim Ahmed (Journal of Islamic Sciences, 2020)
The aim of this research is to shed light on the contents of the Da`wah sites on the Internet and to achieve the goals of the research, a descriptive-analytical approach has been used by analyzing the content of a number of Da`wah websites. The study sample consisted of three Da`wah sites (Islam Today, the Da`wah website), And Dar Al Salam for Islamic Da`wah), which is the most widespread on the Internet, and the analysis of the questionnaire, which consisted of (146) participants.Among the most important findings of the research is that the Islamic Da`wah sites include many windows, articles, and books that serve the Islamic Da`wa and contribute effectively to informing non-Muslims about the image of Islam and creating a positive image and impressions toward the Islamic religion for the browser. The da’wah sites also provided the teachings of the Islamic religion in a way that could be easily understood by non-Muslims, educating Muslims who wish to agree on matters of their religion, increasing their awareness and information about the Islamic religion, and wanting to take fatwas on many topics that concern them. Moreover, the research found that the target audience of the Islamic Da`wah sites were those who want to get to know Islam from the non-Muslim and Muslims, and the general Islamic audience who wants to agree on matters of their religion, and the individuals and institutions working in the field of Islamic Da`wa. The research also concluded that one of the most important goals that most Da`wah sites aim to achieve is to present a message to Muslims and to invite non-Muslims, that is, they have two informational and advocacy messages.Finally, the research found that a strong degree of agreement for the participants, the participants ’agreement on the clarity of the goals used by the Da`wah sites (Islam Today website, the Da`wah Calendar website, and the Dar es Salaam site for Islamic Da`wah) via the Internet on the contents of the Islamic Da`wah, and to a degree of good agreement between the members of the sample for each of the mechanisms The use of the noble hadiths in the propaganda sites via the Internet, methods, and methods of reasoning and fatwas and topics used by the prophetic sites via the Internet, and the values ​​that are concerned with addressing the propaganda sites.
Keywords: Islamic Da`wah sites; the Internet; the contents of Islamic Da`wah sites; Islam Today website; Da`wah Calendar website; Dar Al Salam website for Islamic Da`wah